Polyols and rigid polyurethane foams derived from lignin side-streams of the pulp and paper industry - Fernandes, I.P. (2017)
Lignin is one of the major components of the side-streams of the pulp and paper industries and of the emerging lignocellulosic biore neries. Find new strategies for lignin valorisation, apart from e vironmental issues, will contribute to close the lignocellulosic value-chain. In this context, this work will focus on the synthesis of polyols through oxypropylation and their subsequent incorporation into rigid polyurethane (RPU) foam formulations. Two E. globulus lignin streams were tested: (i) lignin isolated from industrial kraft liquor and (ii) depolymerized lignin resulting from an oxidation process developed at the LA LSRE-LCM to produce vanillin and syringaldehyde. This work is therefore part of the LA LSRE-LCM global strategy towards the consolidation of the integrated process to valorise lignin from the kraft pulp industry, which accounts with more than 25 years of experience.